2022
DOI: 10.2196/35196
|View full text |Cite
|
Sign up to set email alerts
|

App-Based Mindfulness Meditation for People of Color Who Experience Race-Related Stress: Protocol for a Randomized Controlled Trial

Abstract: Background People of color (POC) who experience race-related stress are at risk of developing mental health problems, including high levels of stress, anxiety, and depression. Mindfulness meditation may be especially well suited to help POC cope, given its emphasis on gaining awareness and acceptance of emotions associated with discriminatory treatment. However, mindfulness meditation rarely reaches POC, and digital approaches could reduce this treatment gap by addressing traditional barriers to ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 85 publications
(170 reference statements)
0
1
0
Order By: Relevance
“…Additionally, recent meta-analyses have shown that MBIs may have beneficial effects on vulnerable populations such as people of color 14 . With appropriate adaptations, MBIs have the potential to benefit marginalized groups by helping cultivate emotion regulation, compassion, and awareness skills which may help manage environmental and race-based stressors [15][16][17][18][19] . Nonetheless, results from National Health Interview Survey (NHIS) indicate that in the US, well-educated, NL White and femaleidentifying individuals are more likely to engage in meditation practices relative to lesser educated, non-White, and male groups 10,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent meta-analyses have shown that MBIs may have beneficial effects on vulnerable populations such as people of color 14 . With appropriate adaptations, MBIs have the potential to benefit marginalized groups by helping cultivate emotion regulation, compassion, and awareness skills which may help manage environmental and race-based stressors [15][16][17][18][19] . Nonetheless, results from National Health Interview Survey (NHIS) indicate that in the US, well-educated, NL White and femaleidentifying individuals are more likely to engage in meditation practices relative to lesser educated, non-White, and male groups 10,20 .…”
Section: Introductionmentioning
confidence: 99%